17 How far and how long to do? PCO2 and lactate as possible predictors of survival in traumatic cardiac arrest. (26th April 2019) - Camacho, C; Mancho, G; De Elias, R; Lahoz, Y; Corral, E
Abstract : Background: The factors associated with the survival of Traumatic cardiac arrest (TCA) have been analyzed by many authors. Trying to define a limit on resuscitation efforts: How far and how long to do. The blood analysis has not been described until now, as possible predictor of survival in these patients. Aim: To analyze pH, lactate, bases excess (BE) and pCO2 as possible predictive factors of survival in patients who suffer TCA. Method: Observational Study of patients suffered from TCA in 2016, 2017 and 2018 assisted by our EMS. Collection data from medical records and databases of hospital follow-ups. Data processing and data analysis: quantitative variables are described by central and dispersion measures and qualitative variables by frequency distribution. COR as survival analysis. Excel and SPSS v. 20.0. Results: We analyzed 112 TCA in which CPR is performed and recovered spontaneous circulation 49 (43.75%). After 7 days, 7.14% survived. At the arrival EMS, mean pH was 7.14 (SD 0.15), pCO2 66.57 (ED 20.61), BE −6.09 (ED 6.23) and Lactate 6.51 (ED 3.82). Lactate and PCO2 showed significant relationship in analysis of survival curve after 7 days (p<0, 05). Conclusion: The survival in TCA was 7.14% of patients after 7 days. - Lactate and PCO2 are related to survival at 7 days in our series. – It's necessary more robust studies that can define the factors related to the survival in TCA, but it seems that the biological clock can be one of them. Conflict of interest: There is no conflict of interest. Funding: There is no funding.